Aluminum-based liquid-absorbing core-shell integrated structural component and preparation method thereof, and two-phase heat-saturating device

By laying a wire mesh on the inner surface of the aluminum-based shell using a cold spraying process and spraying aluminum-based powder raw materials to form a liquid absorbent core, the sintering problem in the preparation of the combined preparation of the liquid absorbent core and the shell in the prior art is solved, and an efficient and low-cost preparation method is achieved, and the performance and process simplicity of the liquid absorbent core are improved.

CN119743929APending Publication Date: 2025-04-01WESTERN BAODE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411382699.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing aluminum-based liquid-absorbing core and shell preparation process has technical problems such as difficulty in sintering, powder loss, burning through, deformation and collapse, and the process is complex, energy consumption is high, and the cost is high.

Method used

A wire mesh is laid on the inner surface of the aluminum-based shell by cold spraying, and aluminium-based powder raw materials are sprayed to form a coating to form a liquid absorbent core and combine it with the shell as an integrated structural part to avoid sintering process.

Benefits of technology

The integrated sinter-free preparation of the liquid absorbent core and the shell is realized, the process flow is simplified, the manufacturing cost is reduced, the uniform pore distribution and mechanical properties of the liquid absorbent core are improved, and the capillary force and permeability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119743929A_ABST
    Figure CN119743929A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of heat-spreading devices, and in particular to an aluminum-based liquid-absorbing core-shell integrated structural component and a preparation method thereof, and a two-phase heat-spreading device including the structural component. The structural component includes a shell, a wire mesh, and a coating, all of which are made of aluminum-based materials. The shell has an inner surface for constructing the liquid-absorbing core, the wire mesh is laid on the inner surface of the shell, and the coating is formed on the surface of the wire mesh and the inner surface of the shell by a cold spraying process from a powder raw material. The coating and the wire mesh constitute the liquid-absorbing core, and the liquid-absorbing core is combined with the shell to form an integrated integral structural component. The preparation method mainly comprises: preparing powder raw materials; laying the wire mesh on the inner surface of the shell, spraying the powder raw materials on the surface of the wire mesh and the inner surface of the shell by a cold spraying process, forming a coating and constituting the liquid-absorbing core with the wire mesh, and the liquid-absorbing core is combined with the shell to form an integrated integral structural component; soaking and rinsing the integral structural component to remove residues. It can realize the sintering-free preparation of the liquid-absorbing core and the combination of the liquid-absorbing core and the shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat spreader devices, and in particular to an aluminum-based liquid wick shell integrated structural component, a method for preparing the aluminum-based liquid wick shell integrated structural component, and a two-phase heat spreader device comprising the aluminum-based liquid wick shell integrated structural component. Background Art

[0002] In recent years, electronic power devices have been increasingly miniaturized, high-performance, and integrated. The high heat generation of components will increase their temperature, leading to performance degradation and even thermal runaway. Therefore, how to achieve effective thermal management of electronic devices is the key to solving the current bottleneck in the development of electronic technology.

[0003] Two-phase heat spreaders are heat dissipation devices that use the absorption and release of latent heat during the phase change process of the working fluid to achieve efficient heat transfer. The heat spreader is the main representative of the two-phase heat spreader. It has the advantages of extremely high thermal conductivity, excellent temperature uniformity, reversible transfer direction, variable heat flux density, and no need for additional power, which can meet the needs of high heat flux density heat transfer. At present, the heat spreader has gradually become an ideal heat dissipation device for the current temperature control system, and is widely used in military and civilian fields such as satellites, radars, electronic chips, and servers. As the heat spreader gradually develops towards high efficiency and lightness, the requirements for its processing and manufacturing technology are also getting higher and higher. Traditional copper heat spreaders have the disadvantages of heavy weight and high price, which greatly increases the weight of the equipment and the installation cost. The aluminum heat spreader has become a hot spot in the industry research due to its advantages such as light weight and corrosion resistance.

[0004] As a key component of two-phase heat-saturating devices such as heat spreaders, the wick is mostly prepared by powder, wire mesh sintering or machined grooves. Powder sintered wicks are widely used because of their excellent capillary force. However, it is difficult to sinter aluminum powder. At the same time, the powder sintering process cannot accurately guarantee the thickness and uniformity of the wick and the bonding strength between the wick and the shell. In addition, the manufacturing process of conventional heat spreaders includes complex processes such as wick sintering, wick and shell sintering, support column design and placement, welding and sealing, etc., with low manufacturing efficiency, high energy consumption and cost. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide an aluminum-based liquid absorbent core shell integrated structure and a preparation method thereof, which can realize the sintering-free preparation of the liquid absorbent core and the combination of the liquid absorbent core and the shell.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The present invention provides an aluminum-based liquid-absorbent core-shell integrated structural component, comprising a shell, a wire mesh and a coating, all of which are made of aluminum-based materials. The shell has an inner surface for constructing the liquid-absorbent core, the wire mesh is laid on the inner surface of the shell, the coating is formed on the surface of the wire mesh and the inner surface of the shell by a cold spraying process using powder raw materials, the coating and the wire mesh constitute the liquid-absorbent core, and the liquid-absorbent core and the shell are combined into an integrated integral structural component.

[0008] Preferably, a groove is provided on the inner surface of the shell, and a wire mesh is laid in the groove and a coating is sprayed therein.

[0009] Preferably, multiple layers of wire meshes with different mesh diameters are laid on the inner surface of the shell and / or in the grooves.

[0010] Preferably, a plurality of support columns are formed on the inner surface of the shell by a cold spraying process using powder raw materials to avoid the grooves.

[0011] Preferably, the components of the powder raw material include, by mass percentage: aluminum powder: 60%-80%; aluminum-based alloy powder: 10%-20%; sodium chloride particles: 5%-10%; basalt fiber: 5%-10%.

[0012] Preferably, the content ratio of aluminum powder with a particle size in the range of 5 μm-20 μm, aluminum powder with a particle size in the range of 20 μm-50 μm, and aluminum powder with a particle size in the range of 50 μm-100 μm is 1:2:3.

[0013] The present invention also provides a two-phase heat-saturating device, comprising the aluminum-based liquid-absorbing core-shell integrated structural component as described above.

[0014] The present invention also provides a method for preparing the aluminum-based liquid-absorbent core-shell integrated structural component as described above, which comprises the following steps in sequence: step S1, preparing a powder raw material; step S2, laying a wire mesh on the inner surface of the shell, and using a cold spraying process to spray the powder raw material on the surface of the wire mesh and the inner surface of the shell to form a coating and form a liquid-absorbent core with the wire mesh, and the liquid-absorbent core and the shell are combined into an integrated integral structural component; step S3, soaking and rinsing the integral structural component to remove residues.

[0015] Preferably, step S2 includes in sequence: step S2-1, processing a groove on the inner surface of the shell; step S2-2, laying a wire mesh in the groove as the in-groove wire mesh, and using a cold spraying process to spray powdered raw materials on the in-groove wire mesh and the surface of the groove; step S2-3, laying a wire mesh on the inner surface of the shell as a skeleton wire mesh, and using a cold spraying process to spray powdered raw materials on the surface of the skeleton wire mesh and the inner surface of the shell.

[0016] Preferably, in step S2-3, when the powder raw material is sprayed onto the surface of the skeleton wire mesh and the inner surface of the shell by a cold spraying process, a plurality of support columns are formed on the inner surface of the shell avoiding the grooves by controlling the residence time of the spray gun.

[0017] Compared with the prior art, the present invention has significant improvements:

[0018] The invention adopts a cold spraying process to spray aluminum-based powder raw materials on a silk screen laid on the inner surface of a shell to form an aluminum-based coating, directly integrates the aluminum-based powder raw materials, the silk screen and the shell through cold spraying, constructs a liquid absorbent core on the inner surface of the shell, and combines the liquid absorbent core and the shell into an integrated integral structural member, and the aluminum-based liquid absorbent core is directly integrated with the aluminum-based shell without sintering to form the integrated preparation, thereby avoiding the technical difficulties such as difficult sintering of aluminum powder, powder loss, burn-through, deformation and collapse faced by the sintering process in the preparation process of the liquid absorbent core and the liquid absorbent core shell, greatly simplifying the process flow, and being able to effectively reduce the manufacturing cost, and at the same time, the aluminum-based powder raw materials can be evenly distributed on the silk screen through the cold spraying process, and the thickness and porosity of the liquid absorbent core can be precisely controlled by adjusting the number of cold spraying and the spraying parameters, so as to improve the bonding strength of the powder raw materials and the silk screen, so that the liquid absorbent core has uniform pore distribution and excellent mechanical properties, and effectively balances and regulates the capillary force and permeability of the liquid absorbent core. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of an aluminum-based liquid-absorbing core shell integrated structure according to an embodiment of the present invention.

[0020] Figure 2 It is a schematic diagram of stacking screens in the grooves of the aluminum-based liquid-absorbing core shell integrated structure according to an embodiment of the present invention.

[0021] Figure 3 It is a schematic diagram of stacking skeleton wire meshes in the aluminum-based liquid-absorbing core shell integrated structure of an embodiment of the present invention.

[0022] The reference numerals are described as follows:

[0023] 1 Housing

[0024] 10 Liquid injection port

[0025] 2 Silkscreen

[0026] 2a Wire mesh in the groove

[0027] 2b Skeleton wire mesh

[0028] 3 Coating

[0029] 4 Support columns DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings. These embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0031] In the description of the present invention, it should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0032] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0033] Furthermore, in the description of the present invention, unless otherwise specified, “plurality” means two or more.

[0034] like Figures 1 to 3 The figure shows an embodiment of the aluminum-based liquid wick shell integrated structure provided by the present invention. The aluminum-based liquid wick shell integrated structure of this embodiment is used for a two-phase heat-dissipating device, which is preferably a heat-dissipating plate, or a heat pipe or a liquid cooling plate with a porous layer or a direct cooling plate with a porous layer.

[0035] The aluminum-based liquid-absorbing core shell integrated structural component of this embodiment includes a shell 1, a wire mesh 2 and a coating 3, and the shell 1, the wire mesh 2 and the coating 3 are all made of aluminum-based materials. The shell 1 has an inner surface for constructing the liquid-absorbing core, and a liquid injection port 10 connected to the space on one side of the inner surface of the shell 1 is provided on one side of the shell 1. The liquid-absorbing core is a capillary structure, which is used to provide capillary force to drive the condensed working fluid in the two-phase heat equalizing device to reflux. The wire mesh 2 is laid on the inner surface of the shell 1, and the coating 3 is formed on the surface of the wire mesh 2 and the inner surface of the shell 1 by a cold spraying process from a powder raw material. The coating 3 and the wire mesh 2 constitute the liquid-absorbing core, and the liquid-absorbing core is combined with the shell 1 as an integrated integral structural component.

[0036] The cold spraying process has the advantages of high efficiency and precision. The coating prepared by the cold spraying process has excellent surface formability and surface quality, without defects such as burrs and cracks. In addition, the cold spraying process can customize different coating thicknesses, and can achieve coating requirements from micrometers to millimeters. Compared with the preparation of porous wicks by powder sintering, the cold spraying process has obvious advantages: easy operation and lower energy consumption; extremely high production efficiency, the spraying speed forming efficiency can be as high as 80%; it can realize the preparation of powder / matrix composite materials with different physical and chemical properties, and the surface coating can achieve a high level of surface roughness. During the operation of the porous wick, the rough surface is the dominant nucleation site for the boiling of the liquid working fluid, which is more conducive to the boiling and gasification of the working fluid, thereby promoting the heat transfer and heat conduction of the two-phase heat equalizing device.

[0037] The aluminum-based liquid-absorbing core-shell integrated structural component of this embodiment adopts a cold spraying process to spray aluminum-based powder raw materials on the wire mesh 2 laid on the inner surface of the shell 1 to form an aluminum-based coating 3. The aluminum-based powder raw materials, the wire mesh 2 and the shell 1 are directly integrated by cold spraying, and a liquid-absorbing core is constructed on the inner surface of the shell 1. The liquid-absorbing core and the shell 1 are combined into an integrated integral structural component. The aluminum-based liquid-absorbing core is directly integrated with the aluminum-based shell 1 without sintering, thereby avoiding the sintering process of the liquid-absorbing core and the liquid-absorbing core shell combination preparation process. The technical difficulties faced by the bonding process such as difficult sintering of aluminum powder, powder loss, burn-through, deformation and collapse have been greatly simplified, which can effectively reduce the manufacturing cost. At the same time, the cold spraying process can achieve uniform distribution of aluminum-based powder raw materials on the wire mesh 2. By adjusting the number of cold spraying and spraying parameters, the thickness and porosity of the liquid absorbent core can be precisely controlled, and the bonding strength between the powder raw material and the wire mesh 2 can be improved, so that the liquid absorbent core has uniform pore distribution and excellent mechanical properties, which effectively balances and regulates the capillary force and permeability of the liquid absorbent core.

[0038] In this embodiment, preferably, a groove is provided on the inner surface of the shell 1, and a wire mesh 2 is laid in the groove and sprayed with a coating 3. By processing the groove on the inner surface of the shell 1, the contact thermal resistance between the liquid wick and the inner surface of the shell 1 is reduced. On this basis, a wire mesh 2 is laid in the groove and sprayed with a coating 3 to form a groove liquid wick. The groove liquid wick has the advantages of high permeability and high thermal conductivity, and can enhance the capillary performance of the liquid wick while improving the liquid storage of the two-phase heat equalizing device, thereby improving the limit heat transfer power of the two-phase heat equalizing device and preventing the two-phase heat equalizing device from being partially burned dry. The design of laying a wire mesh 2 in the groove can promote the condensed liquid of the two-phase heat equalizing device to flow back to the wire mesh 2, avoiding the liquid blocking the steam channel and causing the temperature equalization performance to be reduced. Preferably, a plurality of grooves are provided on the inner surface of the shell 1, and the plurality of grooves are evenly spaced on the inner surface of the shell 1, and a wire mesh 2 is laid in each groove and sprayed with a coating 3. The number and spacing of the grooves can be adaptively designed according to the size of the shell 1. The depth of the groove is preferably 2 mm to 5 mm.

[0039] In this embodiment, preferably, multiple layers of wire mesh 2 with different mesh diameters are laid in the groove on the inner surface of the shell 1, and the wire mesh 2 laid in the groove is used as the inner groove wire mesh 2a. The number of layers of the inner groove wire mesh 2a is not limited, and can be two or more layers. The mesh diameter of the inner groove wire mesh 2a is preferably 50μm-350μm, and the best is 50μm-150μm. By laying multiple layers of wire mesh 2 with different mesh diameters in the groove, the mechanical properties and capillary properties of the groove liquid absorbent core can be enhanced, thereby strengthening the overall mechanical properties and capillary properties of the aluminum-based liquid absorbent core shell integrated structure. At the same time, by adjusting the arrangement of the inner groove wire mesh 2a, the powder raw material is graded with the inner groove wire mesh 2a with different mesh diameters, so that the groove liquid absorbent core has a uniform pore structure and a higher porosity, and the permeability of the groove liquid absorbent core is effectively regulated. Preferably, the inner groove wire mesh 2a is stacked and arranged in the groove in a manner that the mesh diameter gradually increases from bottom to top.

[0040] In this embodiment, preferably, multiple layers of wire mesh 2 with different mesh diameters are laid on the inner surface of the shell 1, and the wire mesh laid on the inner surface of the shell 1 is used as the skeleton wire mesh 2b, which is laid on the inner surface of the shell 1 and is located above the groove. The number of layers of the skeleton wire mesh 2b is not limited, and can be two or more layers. The mesh diameter of the skeleton wire mesh 2b is preferably 50μm-350μm, and the best is 150μm-350μm. By laying multiple layers of wire mesh 2 with different mesh diameters on the inner surface of the shell 1, the mechanical properties and capillary properties of the liquid absorbent core constructed on the inner surface of the shell 1 can be enhanced, thereby strengthening the overall mechanical properties and capillary properties of the aluminum-based liquid absorbent core shell integrated structure. At the same time, by adjusting the arrangement of the skeleton wire mesh 2b, the powder raw material is graded with the skeleton wire mesh 2b with different mesh diameters, so that the liquid absorbent core has a uniform pore structure and a higher porosity, and the permeability of the liquid absorbent core is effectively regulated. Preferably, the skeleton wire meshes 2b are stacked and arranged in sequence on the inner surface of the shell 1 in a manner that the diameter of the mesh holes gradually decreases from bottom to top.

[0041] In this embodiment, preferably, a plurality of support columns 4 are formed on the inner surface of the shell 1 by a cold spraying process from a powder raw material avoiding the groove, that is, the support columns 4 are arranged at the position between the grooves on the inner surface of the shell 1. The support columns 4 play the role of supporting the shell of the two-phase heat equalizing device, reducing the steam resistance in the two-phase heat equalizing device, and improving the heat transfer efficiency. When the powder raw material is sprayed on the surface of the wire mesh 2 (skeleton wire mesh 2b) and the inner surface of the shell 1 by the cold spraying process, by controlling the spray gun residence time, a plurality of support columns 4 can be formed on the inner surface of the shell 1 avoiding the groove. Thus, the support columns 4 of various required sizes can be formed by one spraying only by the cold spraying process control, so that the preparation of the support columns 4 does not need to be rinsed and placed separately, and the manufacturing process is more simplified. The number and size of the support columns 4 are not limited, and can be adaptively designed according to the size of the shell 1 and the groove. Preferably, a plurality of support columns 4 are evenly spaced at appropriate density at the position between the grooves on the inner surface of the shell 1 to provide sufficient support force and stability.

[0042] In this embodiment, preferably, the components of the powder raw material used for cold spraying to form the coating 3 include, by mass percentage: aluminum powder: 60%-80%; aluminum-based alloy powder: 10%-20%; sodium chloride particles: 5%-10%; basalt fiber: 5%-10%.

[0043] The aluminum powder is spherical aluminum powder, and the particle size of the aluminum powder is preferably 30μm-150μm. Preferably, in the powder raw material, the content ratio of aluminum powder with a particle size in the range of 5μm-20μm, aluminum powder with a particle size in the range of 20μm-50μm, and aluminum powder with a particle size in the range of 50μm-100μm is 1:2:3. By controlling the particle grading ratio of aluminum powders with different particle sizes, the liquid absorbent core can have a uniform pore structure and a higher porosity, increase the specific surface area of ​​the liquid absorbent core, improve the capillary force of the liquid absorbent core, and enhance the liquid phase flow rate during the operation of the liquid absorbent core, thereby enhancing the thermal conductivity of the two-phase heat balancing device.

[0044] The aluminum-based alloy powder is one or more non-spherical powders of Al-Si series, Al-Mg series, and Al-Cu series alloys, and the particle size of the aluminum-based alloy powder is preferably 50 μm-100 μm. Adding aluminum-based alloy powder to the powder raw material can form a uniform alloy film on the surface of the liquid-absorbing core formed by the wire mesh 2 and the coating 3, and has the effect of anti-corrosion and anti-oxidation.

[0045] Sodium chloride particles are analytically pure reagents. Sodium chloride particles are added to the powder raw materials to use them as pore-forming agents. Sodium chloride particles are stable in the powder raw materials and are easily soluble in water and easy to remove. After the sodium chloride particles are removed, a large number of micropores are formed on the surface of the liquid-absorbing core, which significantly increases the specific surface area of ​​the coating 3.

[0046] The diameter of the basalt fiber is preferably less than 5 μm, and the aspect ratio is preferably 10: 1. Adding basalt fiber to the powder raw material can strengthen the strength of the wire mesh 2, ensure the firmness and flatness of the wick, thereby improving the mechanical properties of the wick, and the mutual construction of basalt fibers in the wick can also improve the capillary force of the wick, so it can effectively improve the thermal conductivity of the two-phase heat-balancing device.

[0047] The amount of basalt fiber added to the powder raw material needs to comprehensively consider the reinforcing effect of the basalt fiber addition ratio, the thickness of the wick, the capillary force of the wick, and other issues. The strength of the wick increases with the increase of the mass ratio of basalt fiber in the powder raw material. When the mass percentage of basalt fiber is less than 5%, it basically cannot play a reinforcing role; but when the mass percentage of basalt fiber exceeds 10%, the strength of the wick will be significantly reduced. This is because when the amount of basalt fiber added is too much, the basalt fiber will be difficult to disperse during the cold spraying powder raw material spraying process, resulting in excessive bridging. When the powder raw material is combined with the screen for molding, the excessive fiber volume content will cause the aluminum-based powder and the screen to be bonded and blocked, thereby reducing the role of the powder in the wick in transferring the load, and the fiber does not play a reinforcing role, so the strength of the wick decreases. Therefore, setting the mass percentage of basalt fiber in the powder raw material to 5%-10% can well enhance the mechanical properties of the liquid absorbent core. Combined with the support column 4 directly formed by the cold spraying process, the aluminum-based liquid absorbent core shell integrated structure of this embodiment has sufficient strength, which can effectively prevent the two-phase heat equalizing device from deforming during operation.

[0048] Based on the aluminum-based liquid absorbing core shell integrated structure of the present invention, an embodiment of the present invention also provides a two-phase heat-saturating device, and the two-phase heat-saturating device of this embodiment includes the aluminum-based liquid absorbing core shell integrated structure mentioned above in this embodiment. The two-phase heat-saturating device of this embodiment is preferably a heat-saturating plate, and the two-phase heat-saturating device of this embodiment can also be a heat pipe or a liquid cooling plate with a porous layer or a direct cooling plate with a porous layer. When the two-phase heat-saturating device of this embodiment is prepared by using the aluminum-based liquid absorbing core shell integrated structure mentioned above in this embodiment, a plurality of the above-mentioned aluminum-based liquid absorbing core shell integrated structures can be combined together by sintering or welding once as needed, and the powder raw material in the coating 3 in the above-mentioned aluminum-based liquid absorbing core shell integrated structure is melted into a liquid phase in the subsequent sintering or welding process, so that the metallurgical bonding between the combined aluminum-based liquid absorbing core shell integrated structures is achieved, thereby realizing the manufacture of the two-phase heat-saturating device. Due to the high permeability of the wire mesh 2 in the aluminum-based liquid absorbing core shell integrated structure, the subsequent sintering or welding process will not affect the capillary force and porosity combination of the liquid absorbing core. Based on the ratio of aluminum powder and aluminum-based alloy powder in the powder raw material, the powder raw material and the aluminum-based wire mesh 2 are bonded together by melting the aluminum-based alloy powder in the subsequent sintering or welding process, so that the absorbent core, the absorbent core and the shell can achieve stronger bonding strength in the subsequent sintering or welding process, thereby increasing the adhesion between the powder material in the absorbent core and the aluminum-based wire mesh 2.

[0049] Based on the aluminum-based liquid absorbent core shell integrated structure of the present invention, the present invention also provides a method for preparing the aluminum-based liquid absorbent core shell integrated structure as described above. The method for preparing the aluminum-based liquid absorbent core shell integrated structure of this embodiment includes the following steps in sequence.

[0050] Step S1, preparing powder raw materials. According to the ratio of the components and the particle size requirements of the powder raw materials used for cold spraying to form the coating 3 in the above-mentioned aluminum-based liquid-absorbing core-shell integrated structure of this embodiment, prepare corresponding aluminum powder, aluminum-based alloy powder, sodium chloride particles and basalt fiber as raw materials and mix them by wet method, then add all the raw materials into anhydrous ethanol according to the ratio of the powder raw materials, vacuumize and stir, then put them into a vacuum oven for vacuum drying, and after forming the mixed raw materials, grind and sieve them to prepare powder raw materials.

[0051] Step S2, laying the wire mesh 2 on the inner surface of the shell 1, and using a cold spraying process to spray the powder raw material on the surface of the wire mesh 2 and the inner surface of the shell 1 to form a coating 3 and form a liquid wick with the wire mesh 2, and the liquid wick is combined with the shell 1 as an integral structural member. In step S2, first prepare multiple layers of aluminum-based wire meshes 2 with different mesh diameters, and the mesh diameter of the wire mesh 2 is preferably 50μm-350μm. These wire meshes 2 are successively placed in an acidic solution for ultrasonication, deionized water washing, and vacuum oven drying. On this basis, step S2 preferably includes the following steps S2-1 to S2-3 in sequence.

[0052] Step S2-1, machining grooves on the inner surface of the housing 1. Preferably, according to the size of the housing 1, a plurality of grooves with an interval of 1 mm and a depth of 2 mm-5 mm are machined on the inner surface of the housing 1.

[0053] Step S2-2, laying a wire mesh 2 in each groove as the in-groove wire mesh 2a. Preferably, multiple layers of in-groove wire mesh 2a are laid in each groove, and the multiple layers of in-groove wire mesh 2a are preferably stacked and arranged in the groove in a manner that the mesh diameter gradually increases from bottom to top. The mesh diameter of the in-groove wire mesh 2a is preferably 50μm-150μm. Then, a cold spraying process is used to spray the powder raw material on the surface of the in-groove wire mesh 2a and the groove to construct a groove wick, and the powder raw material, the in-groove wire mesh 2a and the groove are sprayed and combined in an integrated manner. Preferably, the powder raw material is first sprayed along the groove wall in a circle, the edge of the in-groove wire mesh 2a is combined with the edge of the groove, and then the powder raw material is evenly sprayed on the in-groove wire mesh 2a, the bonding strength between the in-groove wire mesh 2a and the groove is strengthened, and the capillary properties of the in-groove wire mesh 2a are enhanced at the same time, that is, the capillary properties of the constructed groove wick are enhanced.

[0054] Step S2-3, laying the wire mesh 2 as the skeleton wire mesh 2b on the inner surface of the shell 1, the skeleton wire mesh 2b is laid on the inner surface of the shell 1 and is located above the groove. The skeleton wire mesh 2b is preferably stacked and laid with multiple layers, and the multi-layer skeleton wire mesh 2b is preferably stacked and arranged in sequence on the inner surface of the shell 1 in a manner that the mesh diameter gradually decreases from bottom to top. The mesh diameter of the skeleton wire mesh 2b is preferably 150μm-350μm. Then the powder raw material is sprayed on the surface of the skeleton wire mesh 2b and the inner surface of the shell 1 by a cold spraying process, so as to construct a liquid wick on the inner surface of the shell 1, and the powder raw material, the skeleton wire mesh 2b and the shell 1 are sprayed and combined in an integrated manner. Preferably, the powder raw material is first sprayed along the edge of the shell 1, the edge of the skeleton wire mesh 2b is combined with the edge of the shell 1, and then the powder raw material is evenly sprayed on the skeleton wire mesh 2b, and the bonding strength of the skeleton wire mesh 2b with the shell 1 and the inner wire mesh 2a in the groove below is strengthened.

[0055] Furthermore, in step S2-3, when the powder raw material is sprayed on the surface of the skeleton wire mesh 2b and the inner surface of the shell 1 by the cold spraying process, a plurality of support columns 4 are formed on the inner surface of the shell 1 avoiding the grooves by controlling the spray gun residence time. Thus, the support columns 4 of various required sizes can be formed by one spraying only by the cold spraying process control, so that the preparation of the support columns 4 does not require separate washing and placement, and the manufacturing process is further simplified. The support columns 4 are prepared by the cold spraying process at the positions between the grooves on the inner surface of the shell 1 to reduce the steam resistance and improve the heat transfer efficiency, which can not only effectively improve the capillary force of the liquid wick, but also ensure its strength and corrosion resistance.

[0056] At this point, the aluminum-based liquid-absorbent core shell integrated structure of this embodiment is obtained.

[0057] Preferably, the cold spraying process parameters in step S2-2 and step S2-3 are: the spraying medium is nitrogen or argon or other inert gas; the spraying temperature is 100℃-300℃; the air pressure is 1.0Mpa-5.0Mpa; the spray gun flow rate is 10mm / s-50mm / s; the spraying distance is 10mm-50mm; when the support column 4 is prepared by the cold spraying process at the position between the grooves on the inner surface of the shell 1, the spray gun residence time is 3s-15s.

[0058] Step S3, soaking and rinsing the whole structure to remove the residue. Preferably, the aluminum-based liquid-absorbing core shell integrated structure obtained by the above steps S1 and S2 is soaked in deionized water for 30 minutes, then repeatedly rinsed and vacuum dried to remove the residual pore-forming agent.

[0059] At this point, the finished product of the aluminum-based liquid-absorbent core-shell integrated structural component of this embodiment is obtained.

[0060] Three specific embodiments and three comparative examples of the method for preparing the aluminum-based liquid absorbent core shell integrated structural member of the present embodiment are provided below to further describe in detail the method for preparing the aluminum-based liquid absorbent core shell integrated structural member of the present embodiment and the performance of the prepared aluminum-based liquid absorbent core shell integrated structural member.

[0061] Embodiment 1:

[0062] The first specific embodiment of the method for preparing the aluminum-based liquid-absorbing core shell integrated structure of this embodiment includes the following steps in sequence.

[0063] Step S1, prepare raw materials: 300g spherical aluminum powder (including 50g aluminum powder with a particle size of 10μm, 100g aluminum powder with a particle size of 40μm, and 150g aluminum powder with a particle size of 80μm), 100g non-spherical aluminum-based alloy powder (Al-Si system, average particle size of 70μm), 50g sodium chloride particles (analytical grade), and 50g basalt fiber (diameter <5μm, aspect ratio of 10:1). Add all raw materials to 1000mL of anhydrous ethanol to ensure that the raw materials are completely soaked, and use an electric stirrer to stir at room temperature for 2h to ensure uniform mixing. The mixture is then transferred to a vacuum oven and vacuum dried at 80°C for 24h to remove ethanol and ensure that the raw materials are completely dry. Use a sieve with a particle size of 150 mesh to sieve the dried mixture, and the sieved material is the powder raw material.

[0064] Step S2, prepare 5 layers of aluminum-based wire mesh 2: the mesh diameters of each layer of wire mesh 2 are 300 μm, 200 μm, 150 μm, 100 μm, and 50 μm respectively; place each layer of wire mesh 2 in a 5% hydrochloric acid solution, ultrasonically treat for 10 minutes to remove surface impurities, then rinse each layer of wire mesh 2 with deionized water, and then dry in a vacuum oven. On this basis, the following steps S2-1 to S2-3 are performed in sequence.

[0065] Step S2-1, a plurality of grooves with an interval of 1 mm and a depth of 2 mm-5 mm are prepared on the inner surface of the aluminum alloy shell 1 (with a size of 100 mm×100 mm×5 mm) by machining.

[0066] Step S2-2, laying two layers of screen 2 (the mesh diameter of the lower layer is 50 μm, and the mesh diameter of the upper layer is 100 μm) in sequence in the groove as the in-groove screen 2a. The shell 1 with powder raw materials, processed grooves and groove screen 2a laid in the grooves is placed in a cold spraying device, nitrogen is used as the spraying medium, the spraying temperature is set to 200°C, the air pressure is 3.0Mpa, the spray gun flow rate is 30mm / s, and the spraying distance is 20mm. The powder raw material, the groove screen 2a and the groove are integrated by cold spraying: first, the powder raw material is sprayed along the groove wall in a circle, the edge of the groove screen 2a is combined with the groove edge, and the edge spraying residence time is set to 5s; then the powder raw material is evenly sprayed on the groove screen 2a, and the spraying residence time is set to 3s to ensure that the powder raw material is fully attached to the groove screen 2a and the groove edge and surface, so as to realize the combination of the powder raw material, the groove screen 2a and the groove.

[0067] Step S2-3, lay the remaining three layers of wire mesh 2 in descending order of mesh diameter (the mesh diameter of the lower layer is 300 μm, the mesh diameter of the middle layer is 200 μm, and the mesh diameter of the upper layer is 150 μm) on the inner surface of the shell 1 as the skeleton wire mesh 2b. The powder raw material, skeleton wire mesh 2b and shell 1 are placed in a cold spraying equipment, nitrogen is used as the spraying medium, the spraying temperature is set to 200°C, the air pressure is 3.5Mpa, the spray gun flow rate is 30mm / s, and the spraying distance is 20mm. The powder raw material, skeleton wire mesh 2b and shell 1 are integrated by cold spraying: first, the powder raw material is sprayed along the edge of the shell 1 in a circle to combine the edge of the skeleton wire mesh 2b with the edge of the shell 1, and the edge spraying residence time is set to 6s; then the powder raw material is evenly sprayed on the skeleton wire mesh 2b to ensure that the powder raw material is fully attached to the edge and surface of the skeleton wire mesh 2b and the shell 1, and the cold spraying parameters are controlled to strengthen the bonding strength between the skeleton wire mesh 2b and the shell 1 and the inner wire mesh 2a in the groove below. At the same time, the spraying program is set, and by adjusting the nozzle and spraying parameters, a series of small cylinders with a diameter of about 1 mm and a height of about 0.5 mm are sprayed in sequence at intervals of 5 mm at positions between the grooves on the inner surface of the shell 1 as support columns 4. The support columns 4 are evenly distributed and have appropriate density, providing sufficient support force and stability. Thus, an aluminum-based liquid-absorbing core shell integrated structure is obtained.

[0068] Step S3, placing the prepared aluminum-based liquid-absorbing core-shell integrated structure in 500mL of deionized water and soaking it for 30 minutes to dissolve and remove the residual sodium chloride particles. Then rinse it repeatedly with clean water to ensure that all residues are thoroughly removed. Finally, the aluminum-based liquid-absorbing core-shell integrated structure is placed in a vacuum oven for drying to ensure complete drying. So far, a finished aluminum-based liquid-absorbing core-shell integrated structure is obtained.

[0069] Embodiment 2:

[0070] A second specific embodiment of the method for preparing the aluminum-based liquid-absorbing core-shell integrated structural member of this embodiment includes the following steps in sequence.

[0071] Step S1, prepare raw materials: 300g spherical aluminum powder (including 50g aluminum powder with a particle size of 10μm, 100g aluminum powder with a particle size of 40μm, and 150g aluminum powder with a particle size of 80μm), 100g non-spherical aluminum-based alloy powder (Al-Si system, average particle size of 70μm), 50g sodium chloride particles (analytical grade), and 50g basalt fiber (diameter <5μm, aspect ratio of 10:1). Add all raw materials to 1000mL of anhydrous ethanol to ensure that the raw materials are completely soaked, and use an electric stirrer to stir at room temperature for 2h to ensure uniform mixing. The mixture is then transferred to a vacuum oven and vacuum dried at 80°C for 24h to remove ethanol and ensure that the raw materials are completely dry. Use a sieve with a particle size of 150 mesh to sieve the dried mixture, and the sieved material is the powder raw material.

[0072] Step S2, prepare 7 layers of aluminum-based wire mesh 2: the mesh diameters of each layer of wire mesh 2 are 350 μm, 300 μm, 250 μm, 200 μm, 150 μm, 100 μm, and 50 μm respectively; place each layer of wire mesh 2 in a 5% hydrochloric acid solution, ultrasonically treat for 10 minutes to remove surface impurities, then rinse each layer of wire mesh 2 with deionized water, and then dry in a vacuum oven. On this basis, the following steps S2-1 to S2-3 are performed in sequence.

[0073] Step S2-1, a plurality of grooves with an interval of 1 mm and a depth of 2 mm-5 mm are prepared on the inner surface of the aluminum alloy shell 1 (with a size of 100 mm×100 mm×5 mm) by machining.

[0074] Step S2-2, laying two layers of screen 2 (the mesh diameter of the lower layer is 50 μm, and the mesh diameter of the upper layer is 100 μm) in sequence in the groove as the in-groove screen 2a. The shell 1 with powder raw materials, processed grooves and groove screen 2a laid in the grooves is placed in a cold spraying device, nitrogen is used as the spraying medium, the spraying temperature is set to 200°C, the air pressure is 3.0Mpa, the spray gun flow rate is 30mm / s, and the spraying distance is 20mm. The powder raw material, the groove screen 2a and the groove are integrated by cold spraying: first, the powder raw material is sprayed along the groove wall in a circle, the edge of the groove screen 2a is combined with the groove edge, and the edge spraying residence time is set to 5s; then the powder raw material is evenly sprayed on the groove screen 2a, and the spraying residence time is set to 3s to ensure that the powder raw material is fully attached to the groove screen 2a and the groove edge and surface, so as to realize the combination of the powder raw material, the groove screen 2a and the groove.

[0075] Step S2-3, lay the remaining five layers of wire mesh 2 in order of mesh diameter from large to small (the mesh diameters of the wire mesh 2 from bottom to top are 350μm, 300μm, 250μm, 200μm, and 150μm, respectively) on the inner surface of the shell 1 as the skeleton wire mesh 2b. The powder raw material, skeleton wire mesh 2b and shell 1 are placed in a cold spraying equipment, nitrogen is used as the spraying medium, the spraying temperature is set to 200°C, the air pressure is 3.5Mpa, the spray gun flow rate is 30mm / s, and the spraying distance is 20mm. The powder raw material, skeleton wire mesh 2b and shell 1 are integrated by cold spraying: first, the powder raw material is sprayed along the edge of the shell 1 in a circle to combine the edge of the skeleton wire mesh 2b with the edge of the shell 1, and the edge spraying residence time is set to 6s; then the powder raw material is evenly sprayed on the skeleton wire mesh 2b to ensure that the powder raw material is fully attached to the edge and surface of the skeleton wire mesh 2b and the shell 1, and the cold spraying parameters are controlled to strengthen the bonding strength between the skeleton wire mesh 2b and the shell 1 and the inner wire mesh 2a in the groove below. At the same time, the spraying program is set, and by adjusting the nozzle and spraying parameters, a series of small cylinders with a diameter of about 1 mm and a height of about 0.5 mm are sprayed in sequence at intervals of 5 mm at positions between the grooves on the inner surface of the shell 1 as support columns 4. The support columns 4 are evenly distributed and have appropriate density, providing sufficient support force and stability. Thus, an aluminum-based liquid-absorbing core shell integrated structure is obtained.

[0076] Step S3, placing the prepared aluminum-based liquid-absorbing core-shell integrated structure in 500mL of deionized water and soaking it for 30 minutes to dissolve and remove the residual sodium chloride particles. Then rinse it repeatedly with clean water to ensure that all residues are thoroughly removed. Finally, the aluminum-based liquid-absorbing core-shell integrated structure is placed in a vacuum oven for drying to ensure complete drying. So far, a finished aluminum-based liquid-absorbing core-shell integrated structure is obtained.

[0077] Embodiment 3:

[0078] The third specific embodiment of the method for preparing the aluminum-based liquid-absorbing core shell integrated structure of this embodiment includes the following steps in sequence.

[0079] Step S1, prepare raw materials: 400g spherical aluminum powder (including 50g aluminum powder with a particle size of 10μm, 100g aluminum powder with a particle size of 40μm, and 150g aluminum powder with a particle size of 80μm), 50g non-spherical aluminum-based alloy powder (Al-Si system, average particle size of 70μm), 25g sodium chloride particles (analytical grade), and 25g basalt fiber (diameter <5μm, aspect ratio of 10:1). Add all raw materials to 1000mL of anhydrous ethanol to ensure that the raw materials are completely soaked, and use an electric stirrer to stir at room temperature for 2h to ensure uniform mixing. The mixture is then transferred to a vacuum oven and vacuum dried at 80°C for 24h to remove ethanol and ensure that the raw materials are completely dry. Use a sieve with a particle size of 150 mesh to sieve the dried mixture, and the sieved material is the powder raw material.

[0080] Step S2, prepare 5 layers of aluminum-based wire mesh 2: the mesh diameters of each layer of wire mesh 2 are 300 μm, 200 μm, 150 μm, 100 μm, and 50 μm respectively; place each layer of wire mesh 2 in a 5% hydrochloric acid solution, ultrasonically treat for 10 minutes to remove surface impurities, then rinse each layer of wire mesh 2 with deionized water, and then dry in a vacuum oven. On this basis, the following steps S2-1 to S2-3 are performed in sequence.

[0081] Step S2-1, a plurality of grooves with an interval of 1 mm and a depth of 2 mm-5 mm are prepared on the inner surface of the aluminum alloy shell 1 (with a size of 100 mm×100 mm×5 mm) by machining.

[0082] Step S2-2, laying two layers of screen 2 (the mesh diameter of the lower layer is 50 μm, and the mesh diameter of the upper layer is 100 μm) in sequence in the groove as the in-groove screen 2a. The shell 1 with powder raw materials, processed grooves and groove screen 2a laid in the grooves is placed in a cold spraying device, nitrogen is used as the spraying medium, the spraying temperature is set to 200°C, the air pressure is 3.0Mpa, the spray gun flow rate is 30mm / s, and the spraying distance is 20mm. The powder raw material, the groove screen 2a and the groove are integrated by cold spraying: first, the powder raw material is sprayed along the groove wall in a circle, the edge of the groove screen 2a is combined with the groove edge, and the edge spraying residence time is set to 5s; then the powder raw material is evenly sprayed on the groove screen 2a, and the spraying residence time is set to 3s to ensure that the powder raw material is fully attached to the groove screen 2a and the groove edge and surface, so as to realize the combination of the powder raw material, the groove screen 2a and the groove.

[0083] Step S2-3, lay the remaining three layers of wire mesh 2 in descending order of mesh diameter (the mesh diameter of the lower layer is 300 μm, the mesh diameter of the middle layer is 200 μm, and the mesh diameter of the upper layer is 150 μm) on the inner surface of the shell 1 as the skeleton wire mesh 2b. The powder raw material, skeleton wire mesh 2b and shell 1 are placed in a cold spraying equipment, nitrogen is used as the spraying medium, the spraying temperature is set to 200°C, the air pressure is 3.5Mpa, the spray gun flow rate is 30mm / s, and the spraying distance is 20mm. The powder raw material, skeleton wire mesh 2b and shell 1 are integrated by cold spraying: first, the powder raw material is sprayed along the edge of the shell 1 in a circle to combine the edge of the skeleton wire mesh 2b with the edge of the shell 1, and the edge spraying residence time is set to 6s; then the powder raw material is evenly sprayed on the skeleton wire mesh 2b to ensure that the powder raw material is fully attached to the edge and surface of the skeleton wire mesh 2b and the shell 1, and the cold spraying parameters are controlled to strengthen the bonding strength between the skeleton wire mesh 2b and the shell 1 and the inner wire mesh 2a in the groove below. At the same time, the spraying program is set, and by adjusting the nozzle and spraying parameters, a series of small cylinders with a diameter of about 1 mm and a height of about 0.5 mm are sprayed in sequence at intervals of 5 mm at positions between the grooves on the inner surface of the shell 1 as support columns 4. The support columns 4 are evenly distributed and have appropriate density, providing sufficient support force and stability. Thus, an aluminum-based liquid-absorbing core shell integrated structure is obtained.

[0084] Step S3, placing the prepared aluminum-based liquid-absorbing core-shell integrated structure in 500mL of deionized water and soaking it for 30 minutes to dissolve and remove the residual sodium chloride particles. Then rinse it repeatedly with clean water to ensure that all residues are thoroughly removed. Finally, the aluminum-based liquid-absorbing core-shell integrated structure is placed in a vacuum oven for drying to ensure complete drying. So far, a finished aluminum-based liquid-absorbing core-shell integrated structure is obtained.

[0085] Comparative Example 1:

[0086] Comparative Example 1 is a first comparative test of the preparation method of the aluminum-based liquid-absorbing core shell integrated structure compared with the present embodiment. Compared with Example 1, the preparation method of the powder raw material in Comparative Example 1 is the same, and the difference is that Comparative Example 1 uses a sintering process to combine the powder raw material, the wire mesh and the shell into one.

[0087] In Comparative Example 1, a hot press furnace was used as the sintering furnace. Three layers of wire mesh were placed on the inner surface of the aluminum alloy shell, and then the powder raw materials were evenly spread on the three layers of wire mesh. The shell with the wire mesh and powder raw materials stacked in sequence was placed in the hot press furnace, the pressure was adjusted to 1.0T-2.0T, and the vacuum furnace was evacuated to 1×10 -2 Pa-1×10- 3Pa, raise the temperature from room temperature to 200°C at a heating rate of 10°C / min-15°C / min, and then continue to heat it to 500°C-650°C at a heating rate of 5°C / min-10°C / min, keep it warm for 2h, and continue to cool it by introducing argon when the furnace is cooled to below 300°C to obtain an integrated structure of a powder-mesh composite liquid absorbent core and a shell.

[0088] Comparative Example 2:

[0089] Comparative Example 2 is a second comparative test of the preparation method of the aluminum-based liquid-absorbing core shell integrated structure compared with the present embodiment. Compared with Example 1, the difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not set the groove and the inner screen 2a of the groove, nor does it set the skeleton screen 2b, and directly combines the powder raw material with the shell 1 by cold spraying to form the liquid-absorbing core and the shell integrated structure.

[0090] Comparative Example 3:

[0091] Comparative Example 3 is a third comparative test of the preparation method of the aluminum-based liquid-absorbing core shell integrated structural component compared with the present embodiment. Compared with Example 1, Comparative Example 3 is different in that basalt fiber is removed from the composition of the powder raw material, and the other steps are consistent with Example 1 to obtain a powder-net composite liquid-absorbing core and shell integrated structural component.

[0092] Table 1 below shows the porosity, capillary force and tensile strength of the integrated structural parts prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0093] Table 1

[0094]

[0095]

[0096] Among them, the experimental data of Example 1, Example 2 and Example 3 show that the aluminum-based absorbent core-shell integrated structural part prepared by the preparation method of the aluminum-based absorbent core-shell integrated structural part of this embodiment has an average porosity of ≥51% of the absorbent core, a capillary suction height exceeding 1 / 2 of the sample height, and a compressive strength of ≥56Mpa. Compared with the prior art, the aluminum-based absorbent core-shell integrated structural part of this embodiment has a uniform pore density, no defects such as delamination, shedding, and powder loss, and the powder-net composite has good bonding strength with the aluminum alloy shell. The preparation method of the aluminum-based absorbent core-shell integrated structural part of this embodiment can precisely control the thickness and porosity of the absorbent core, and effectively balance and regulate the capillary force and permeability of the absorbent core.

[0097] Compared with Example 1, Example 2 can improve the permeability and mechanical properties of the final product by increasing the number of wire mesh 2 layers.

[0098] Compared with Example 1, Example 3 obtains finished products with different porosities and capillary forces by adjusting the proportion of powder raw material components.

[0099] Compared with the comparative example 1 which adopts the existing composite sintering process, the aluminum-based liquid absorbent core-shell integrated structural part prepared by the preparation method of the aluminum-based liquid absorbent core-shell integrated structural part of the present embodiment can make the powder, mesh and shell tightly connected under the premise of ensuring the porosity, and the strength is greatly improved, thereby avoiding the technical difficulties such as difficult sintering and powder falling faced in the sintering process of the aluminum-based liquid absorbent core, and overcoming the problems of multiple sintering and burn-through, deformation or collapse faced in the sintering composite process of the aluminum-based liquid absorbent core and shell in the conventional method, and the operation is simple, the energy consumption is lower, and the production cost is greatly saved.

[0100] Compared with the preparation method of Example 1 and Comparative Example 2 without adding a wire mesh, the aluminum-based liquid-absorbent core-shell integrated structural component prepared by the preparation method of the aluminum-based liquid-absorbent core-shell integrated structural component of this embodiment, by setting a wire mesh 2 and adjusting the arrangement of the wire mesh 2, makes the liquid-absorbent core have a uniform pore structure and a high porosity, effectively increases the specific surface area of ​​the liquid-absorbent core, significantly improves the capillary force of the liquid-absorbent core, can enhance the flow rate of the working fluid, and improve the thermal conductivity efficiency of the device.

[0101] Compared with the preparation method of Example 1 and Comparative Example 3 without adding basalt fiber, the aluminum-based liquid absorbent core shell integrated structure prepared by the preparation method of the aluminum-based liquid absorbent core shell integrated structure of this embodiment has improved tensile strength, and the mechanical properties of the liquid absorbent core have also been improved, which enhances the service life of the two-phase heat-dissipating device and avoids the collapse and deformation of the two-phase heat-dissipating device during use. In addition, the mutual construction of basalt fibers in the liquid absorbent core can also ensure the capillary force of the liquid absorbent core, thereby enhancing the comprehensive heat transfer efficiency of the two-phase heat-dissipating device.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present invention. These improvements and substitutions should also be regarded as the scope of protection of the present invention.

Claims

1. An aluminum-based liquid-absorbing core shell integrated structural component, characterized in that: It includes a shell, a wire mesh and a coating, all of which are made of aluminum-based materials. The shell has an inner surface for constructing a liquid-absorbing core. The wire mesh is laid on the inner surface of the shell. The coating is formed on the surface of the wire mesh and the inner surface of the shell by a cold spraying process using powder raw materials. The coating and the wire mesh constitute the liquid-absorbing core, and the liquid-absorbing core is combined with the shell to form an integrated integral structural component.

2. The aluminum-based liquid-absorbing core shell integrated structural component according to claim 1, characterized in that: A groove is arranged on the inner surface of the shell, and the wire mesh is laid in the groove and the coating is sprayed therein.

3. The aluminum-based liquid-absorbing core shell integrated structural component according to claim 2, characterized in that: Multiple layers of wire meshes with different mesh diameters are laid on the inner surface of the shell and / or in the groove.

4. The aluminum-based liquid-absorbing core shell integrated structural component according to claim 2, characterized in that: A plurality of support columns are formed on the inner surface of the shell by the cold spraying process from the powder raw material avoiding the groove.

5. The aluminum-based liquid-absorbing core shell integrated structural component according to claim 1, characterized in that: The components of the powder raw material include, by mass percentage: aluminum powder: 60%-80%; aluminum-based alloy powder: 10%-20%; sodium chloride particles: 5%-10%; Basalt fiber: 5%-10%.

6. The aluminum-based liquid-absorbing core shell integrated structure according to claim 5, characterized in that: The content ratio of aluminum powder with a particle size within the range of 5μm-20μm, aluminum powder with a particle size within the range of 20μm-50μm, and aluminum powder with a particle size within the range of 50μm-100μm is 1:2:

3.

7. A two-phase heat distribution device, characterized in that: It comprises an aluminum-based liquid-absorbing core shell integrated structural component as described in any one of claims 1 to 6.

8. A method for preparing an aluminum-based liquid-absorbing core shell integrated structure as claimed in any one of claims 1 to 6, characterized in that: The following steps are included in sequence: Step S1, preparing the powder raw material; Step S2, laying the wire mesh on the inner surface of the shell, and using a cold spraying process to spray the powder raw material on the surface of the wire mesh and the inner surface of the shell to form the coating and the liquid wick together with the wire mesh. The liquid absorbent core and the shell are combined into an integrated integral structural member; Step S3, soaking and rinsing the integral structural part to remove residues.

9. The method for preparing the aluminum-based liquid-absorbing core-shell integrated structural member according to claim 8, characterized in that: The step S2 comprises in sequence: Step S2-1, machining a groove on the inner surface of the shell; Step S2-2, laying the wire mesh in the groove as the in-groove wire mesh, and spraying the powder raw material on the surface of the in-groove wire mesh and the groove by a cold spraying process; Step S2-3: laying the wire mesh as a skeleton wire mesh on the inner surface of the shell, and spraying the powder raw material on the surface of the skeleton wire mesh and the inner surface of the shell by a cold spraying process.

10. The method for preparing the aluminum-based liquid-absorbing core-shell integrated structure according to claim 9, characterized in that: In the step S2-3, when the powder raw material is sprayed onto the surface of the skeleton wire mesh and the inner surface of the shell by the cold spraying process, a plurality of support columns are formed on the inner surface of the shell avoiding the groove by controlling the spray gun residence time.